The birth and growth of modern research on ontologies - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2008)
Recent developments in ontology research in the fields of Library and Information Science (LIS), Computer Sciences, and other related disciplines are examined through a bibliometric survey. Results confirm that the current research surge must be contextualized in terms of Internet developments and, especially, the Semantic Web Project. Research on formal ontologies for knowledge representation is changing the course of research on knowledge organization and representation, and is even causing changes in LIS terminology, as occurred previously with the metadata movement in the field of cataloguing.